PRIORITY OF FISHING PORT EXPANSION IN NORTHERN COAST OF CENTRAL JAVA BASED ON THE SUPPORTING POWER POTENCY - Ernani Lubis; Bey Pane (Indonesian Fisheries Research Journal, 2010)
Existence of port that was capture fisheries activity economic centre has very big roles in supporting capture fisheries development in northern coast of Central Java. Still many fishing port mainly fish landing place that the coqdition and management are very limited if compared to its fisheries progress so needs to expand